Structural and functional characteristics of microbiota in oropharynx of sub-healthy children with gastrointestinal heat retention syndrome differentiated by traditional Chinese medicine - Jianhua Zhen; He Yu; Xiaofei Li; Fei Dong; Zi'an Zheng; Xueyan Ma; Yuxiang Wan; Tiegang Liu; Lu Fan; Xiaohong Gu (Journal of Traditional Chinese Medical Sciences, 2022)
Objective: To explore the structural and functional characteristics of microbiota in oropharynx of sub-healthy children with gastrointestinal heat retention syndrome (GHRS) differentiated by traditional Chinese medicine, and screen the biometric operational taxonomic units (OTUs) to assist the clinical diagnosis. Methods: We recruited children according to the “GHRS diagnostic scale”, collected their oropharyngeal swabs, and sequenced the 16S rDNA V4 region. We described the bacterial structure with alpha-indexes, beta-distances, and relative abundances; moreover, we screened the differential genera/OTUs with Wilcoxon rank-sum test, MetagenomeSeq analysis, and linear discriminant analysis effect size (LEfSe) analysis, in which biometric OTUs were selected to construct the receiver operating characteristic curve to verify the diagnostic value. The bacterial function was predicted with Kyoto Encyclopedia of Genes and Genomes pathways according to 16S rDNA gene by using Phylogenetic Investigation of Communities by Reconstruction of Unobserved States. Results: The study population was composed of 10 children with GHRS and 10 healthy control children. GHRS children were more likely to overeat (gluttony, P = .033). Alpha-indexes, such as Sobs, abundance-based coverage estimator, Bootstrap, and Qstat, were significantly higher in the GHRS group, while beta-distances did not exhibit any significant intergroup differences. There were 9 differently distributed non-predominant genera between the groups in Wilcoxon rank-sum test, as well as 13 non-predominant genera in MetagenomeSeq analysis and 3 non-predominant OTUs in LEfSe analysis. OTU44 and OTU196 were used to construct the receiver operating characteristic curve, and the area under curve was 0.92. Predicted functions showed that pathways related to oxidative phosphorylation and carbon metabolism were enriched in healthy control samples, while the pathway related to renin secretion was remarkably enriched in GHRS samples. Conclusion: Unique oropharyngeal microbial structure and function were identified in GHRS children. OTU44 and OTU196 were specific OTUs, which could be used as biomarkers of GHRS to assist clinical diagnosis.